Focus on Synergistic Bacteriocin-Nanoparticles Enhancing Antimicrobial Activity Assay - Ahmed, M.E.; Al-Awadi, A.Q.; Abbas, A.F.; Ахмед, М.Е.; Аль-Аваді, А.К.; Аббас, А.Ф. (PH "Akademperiodyka" of the NAS of Ukraine, 2023)
Antimicrobial resistance is one of the most significant threats to public health worldwide. As opposed to using traditional antibiotics, which are effective against diseases that are multidrug-resistant, it is vital to concentrate on the most innovative antibacterial compounds. These innate bacterial arsenals under the term «bacteriocins» refer to low-molecularweight, heat-stable, membrane-active, proteolytically degradable, and pore-forming cationic peptides. Due to their ability to attack bacteria, viruses, fungi, and biofilm, bacteriocins appear to be the most promising, currently accessible alternative for addressing the antimicrobial resistance (AMR) problem and minimizing the negative effects of antibiotics on the host’s microbiome. Nano-compounds have shown promise in a variety of applications, including antibacterial agents, drug delivery systems, food and drug packaging elements, functional food formulations, and many more. However, there are certain disadvantages in the chemical production of nanoparticles (NPs), such as toxicity and other negative impacts. Due to the dual action of biological sources combined with metallic NPs, the use of conjugated or green-synthesized nanoparticles has become more widespread during the past ten years. Recently, bacteriocin nanoparticles have emerged as a viable remedy and the most effective antibacterial agent in vitro to overcome some of these limitations.